PENGARUH MERONCE MENGGUNAKAN CANGKANG KERANG BERWARNA TERHADAP MOTORIK HALUS DI TAMAN KANAK-KANAK ASSYOFA KOTA PADANG - Ulandari, Putri; Mayar, Farida; Indra Yeni; Asdi Wirman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Fine motor development is one of the important aspects that need to be stimulated in early childhood because it supports children's readiness in learning and carrying out daily activities. Based on observations at Assyofa Kindergarten Padang, children's fine motor skills had not developed optimally. Learning activities were still dominated by worksheets, coloring, drawing, and stringing using plastic straws, causing children to become less interested and less enthusiastic. This study aimed to determine the effect of stringing colored seashells on children's fine motor skills. The study employed a quantitative approach using a quasi-experimental design. The sample consisted of 42 children, divided into an experimental class (B4) and a control class (B2), with 21 children in each group. Data were collected through observation and analyzed using normality tests, homogeneity tests, and independent sample t-tests with SPSS version 23. The results showed that the average gain score in the experimental class was 3.09, while the control class was -0.33. The hypothesis test showed a significance value (Sig. 2-tailed) of 0.015 < 0.05, indicating a significant effect of stringing colored seashells on children's fine motor skills. Therefore, stringing activities using colored seashells can be used as an alternative learning activity to improve fine motor development in early childhood.